Investigation of the effect of acute badminton training on selected biomotoric parameters - Nurkan Yılmaz (Physical Education of Students, 2022)
Background and Study Aim. One of the fastest racquet sports in the world, badminton is defined as a versatile, explosive sprint sport that requires players to perform intense rhythmic movements with its highly competitive and dynamic feature. The aim of this study is to investigate the effectiveness of 4-week badminton training on some selected biomotoric features in young individuals engaged in recreational sports.